2019
DOI: 10.3390/geosciences9090376
|View full text |Cite
|
Sign up to set email alerts
|

Cyclogenesis and Density Currents in the Middle East and the Associated Dust Activity in September 2015

Abstract: The first 10 days of September 2015 were marked by intense dust activity over the Middle East and the Arabian Peninsula. This study examines the atmospheric conditions at the origin of the large dust storms during this period. We particularly investigate the atmospheric dynamics leading to the development of a large dry cyclone over Iraq on 31 August 2015 which in turn generated an intense dust storm that affected most of the countries around the Arabian Gulf and lasted for 5 days. We found that the cyclone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…Meso-NH is a non-hydrostatic mesoscale model coupled with an online dust emission and transport module [70]. The model has been extensively validated against ground-based, airborne, and satellite datasets [41,[71][72][73] and is very capable of simulating the atmospheric dynamics for dust mobilization, dust emission, and transport pathways as previous studies over Sahara have shown [30,37,[74][75][76]. In this study, the model was run during four days [from 4 February 2019 at 00:00 UTC (Universal Time Coordinated) to 8 February 2019 at 00:00 UTC] over the domain 45…”
Section: Meso-nh Model Simulationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Meso-NH is a non-hydrostatic mesoscale model coupled with an online dust emission and transport module [70]. The model has been extensively validated against ground-based, airborne, and satellite datasets [41,[71][72][73] and is very capable of simulating the atmospheric dynamics for dust mobilization, dust emission, and transport pathways as previous studies over Sahara have shown [30,37,[74][75][76]. In this study, the model was run during four days [from 4 February 2019 at 00:00 UTC (Universal Time Coordinated) to 8 February 2019 at 00:00 UTC] over the domain 45…”
Section: Meso-nh Model Simulationsmentioning
confidence: 99%
“…Cut-off cold lows in the middle and upper troposphere are usually developed over the subtropics and mid-latitudes associated with penetrating deep troughs from high latitudes [30,87,88]. They usually begin as a trough, as was shown on 5 February, and progressively become a closed circulation with a cold core, which may be stationary for days and be extended down to the surface forming a baroclinic system with unstable weather conditions [30,89,90]. The cut-off low in our case was transferred to low levels when it reached central Afghanistan on 6 February and it caused the development of deep convection facilitated by orographic blocking.…”
Section: Synoptic Situationmentioning
confidence: 99%
See 3 more Smart Citations